(untitled) (Rainbow Journal, 2019)
Folk music of Nepal reflects the aesthetic sense of the people and has been preserved by Oral tradition. Religions practiced in Nepal are Hinduism, Buddhism, Islam, Christianity, Jainism, Sikhism, Bon, ancestor worship, and animism. The majority of Nepalese are Hindus and Buddhists too, and these two religions have co-existed in harmony through centuries. Nepal is a multi-lingual, multi-cultural, and multi-diverse country. Being a small country located in between China and India of south Asia, though it has multi-dimensional folk and traditional culture and dances among the many ethnicities, tribes, and indigenous people. Many scattered contributions can be found in the literature but the concise and specific study about the topic is still unexplored. This paper highlighted to explore overall Nepalese culture and folk music and dances which are existed in various places of social life.